HOW IMPORTANT IS A SCHOOL? EXAMINING THE IMPACT OF REMOTENESS FROM A SCHOOL ON CANADIAN COMMUNITIES’ ATTRACTION AND RETENTION OF SCHOOL-AGE CHILDREN - Foster, Karen; Bollman, Ray; Main, Hannah (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
Many Canadian communities, especially rural communities, are concerned about youth outmigration as a cause of population decline, which is associated with fewer services and amenities. Proponents of keeping underattended schools open argue that removing a school from the community means that fewer families will want to live there, and that more families will consider leaving. Others view school closures as a rational response to population decline. Still other perspectives complicate the correlation between schools and population, noting phenomena such as children “learning to leave” and “place attachment” that modulate the temptation to move away. This paper offers an empirical test of discursive connections between school closures and mobilities by studying the population change of school-age children in Canadian census subdivisions indexed by distance to the nearest school. Based on this method, we conclude that there is a positive correlation between the school-age population in a community and proximity to a school in that community. Although our data do not answer the question of whether school closures cause population decline, or such a decline causes school closures, or both, we provide a quantitative foundation on which to ask it.